Nurse Home Visity with Educational Activities in the arterial pressure treatment - Maria de Fátima Mantovani; Juliana Veiga Mottin; Juliana Rodrigues (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
This study aims: to compare the maintenance of the arterial pressure levels on Arterial Hypertension bearings, followed and monitored with educational activities in family (cases) or individualized (control), visited at home monthly and bimonthly respectively. 30 users enrolled in the Hyper tense Treatment Programme have been followed since October 2005, aged between 18 e 65 years old. The data analysis shows that, in the case group 64% kept the weight and the abdominal circumference and 29% reduced these variables; 50% has done regular physical exercises; and, 75% has done medical treatment. In the control group: 38% has presented an increasing on weight and abdominal circumference; 28% started doing regular physical exercises; and, 100% joined the medicament therapy. It was verified improvement adhesion to the treatment and other therapeutical measures, besides the maintenance and the parameters reduction in both groups.